Pathogen‐reduced Ebola virus convalescent plasma: first steps towards standardization of manufacturing and quality control including assessment of Ebola‐specific neutralizing antibodies. Issue 4 (14th January 2016) - Geisen, C.; Kann, G.; Strecker, T.; Wolf, T.; Schüttfort, G.; van Kraaij, M.; MacLennan, S.; Rummler, S.; Weinigel, C.; Eickmann, M.; Fehling, S. K.; Krähling, V.; et al.
Abstract : Background: Ebola virus disease is a public health emergency of international concern, and enormous efforts are being made in the development of vaccines and therapies. Ebola virus convalescent plasma is a promising anti‐infective treatment of Ebola virus disease. Therefore, we developed and implemented a pathogen‐reduced Ebola virus convalescent plasma concept in accordance with national, European and global regulatory framework. Materials and Methods: Ebola virus convalescent plasma manufacture and distribution was managed by a collection centre, two medical centres and an expert group from the European Blood Alliance. Ebola virus convalescent plasma was collected twice with an interval of 61 days from a donor recovering from Ebola virus disease in Germany. After pathogen reduction, the plasma was analysed for Ebola virus‐specific immunoglobulin G (IgG) antibodies and its Ebola virus neutralizing activity. Results: Convalescent plasma could be collected without adverse events. Anti‐Ebola virus IgG titres and Ebola‐specific neutralizing antibodies in convalescent plasma were only slightly reduced after pathogen reduction treatment with S59 amotosalen/UVA. A patient in Italy with Ebola virus disease was treated with convalescent plasma without apparent adverse effects. Discussion: As proof of principle, we describe a concept and practical implementation of pathogen‐reduced Ebola virus convalescent plasma manufacture, quality control and its clinical application to an Ebola virus disease patient.